A Feasibility Study on EUREKA! The Science-Amusement Center - Reyes, Victor C. (College of Engineering, 1996)
Eureka! is a science-amusement center with interactive science exhibits. Its main objective is to propagate the knowledge of science and technology in children. This feasibility study is geared towards determining not just the economic viability of such a project, but also to know its impact on society. A market study was conducted wherein the population of students in the primary and secondary levels in Metro Manila was deemed as the potential market. Market segmentation, mainly by considering geographical location, was used to determine the target market and the market share of Eureka!. The target market is the population of primary and secondary level students residing in Quezon City, Pasig City, Makati City, Mandaluyong City and San Juan. The market share of Eureka! was estimated at 37.12% of the target market at its first year of operation, and will grow to 52.14% on its fifth year of operation. Also, the current supply and demand relationship between the existing science centers and the market was studied. A marketing program was developed and was geared towards making people aware of the existence of Eureka!. During the technical study, it was determined that the location of the science-amusement center would be in Building A, SM Megamall, Mandaluyong City. It was also determined that the interactive science exhibits would either be subcontracted or bought from a supplier of science equipment. Staffing was determined by considering cost of hiring personnel and the comfort and enjoyment of the customers of the center. The total project cost is P 2,324,065.70. During the financial study, it was determined that the project is financially feasible. The Internal Rate of Return is 42.74%. The net income for the first year of operations is P 9,636,000. From the first year to fourth year of operations, net income increases by 30% annually. However, net income decreases by 0.4% on its fifth year mainly because ideal capacity utilization has been reached. The venture remains profitable, however, despite this outcome. From the social profitability study, the cost and benefit of the study were pointed out and then quantified. The organizational study determined the personnel needed to run a small scale science center and the qualifications of these personnel. This project will be funded and owned by Fun Corporation. This is a non-stock corporation run by two brothers-in-law, their wives, and another associate. The Director of the science-amusement center will be one of the owners of Fun Corporation which will lead to close supervision and control of the center by the owners. There will be 14 regular employees, ranging from the Director of the center to the maintenance personnel. There will also be 86 contractual Customer Service Representatives.